Analysis of the objective and preventative treatment and efficacy of therapeutic approaches in women with non-atypical endometrial hyperplasia - O. L. Gromova (Kazimierz Wielki University, 2020)
Non-atypical endometrial hyperplasia (EH) is prone to recurrence and has an unspecified residual monitoring and treatment algorithm. The main factors that influence the possibility of recurrence and progression are not known yet. The objective: examination of the frequency of hyperproliferative endometrial pathology (HPE) in premenopausal women, organization of treatment and prophylactic measures and their influence on the recurrence or progression of HPE. Design of the study: a retrospective observational study. Results of the study: The results of monitoring and treatment were analysed in 380 premenopausal women according to STRAW+10 criteria. The structure was dominated by non-atypycal endomrtrial hyperplasia (EH)- in 356 (93.7%) cases, atypycal hyperplasia (AH) - in 16 (4.2%), endometrial cancer (EC) - in 8 (2.6%). 60 women underwent hysterectomy (24 - AH and EC, 36 - concomitant pathology). Results from 320 women with EH excluding hysterectomy, have been monitored over 3 years. Hormonal treatment with gestagens was given to 138 of 320 women (43.1%), 78 (24.3%) received oral progestins without an interruption for 3 months, 34 (10.6%) for 6 months and 26 (8.1%) received LNG-IUDs 52 mg, in 182 (56.8%) no treatment was provided. The effectiveness of EH therapy in women with LNG-IUDs was achieved in 92.3% of cases, with gestagen treatment at 6 months in 70.6%, and at 3 months in 39.7%. With no therapy, regression of the disease was 28.8%. The incidence of EH at the 3rd year of follow-up in women without treatment was 2.4 times higher than at the 6-month course of oral gestagen therapy (71.4 vs 29.4%) and was not significantly different from the 3-month course (71.4 vs 60.3%). There is a lack of clarity in the treatment and monitoring system for women with EH in the study centres; short timing of gestagen prescriptions are insufficiently effective and contribute to a high rate of recurrence; the LNG IUD showed the best efficacy results (93.7%) and absence of recurrence over the course of the study.